The effect of recycled rubber on the properties of epoxy/ recycled rubber blends filled with carbon black - Najihah Jamil (School of Materials Engineering, Universiti Malaysia Perlis, 2015)
In this research, objectives has been focused on the determination of filler (carbon black) content to reached the percolation threshold.